2013
DOI: 10.1016/j.postharvbio.2012.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Study on differential expression of 1-aminocyclopropane-1-carboxylic acid oxidase genes in table grape cv. Thompson Seedless

Abstract: International audienceAs a consequence of the non-climacteric status of grapes (Vitis vinifera), ethylene biosynthesis and signal transduction have scarcely been studied in this fruit. In spite this drawback, the available information suggests a role for ethylene in ripening grape berries. In this work, we report the identification of three homologous genes that encode 1-aminocyclopropane-1-carboxylic acid oxidase (ACO), a key component of ethylene biosynthesis. A comparison of protein sequences revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Likewise, their results of the evolution of both ACC (1-aminocyclopropane-1-carboxylic acid) content and ACO (ACC oxidase) activity strongly support the increase in ethylene production in grapevines during the early stage of cold stress. Results obtained by Muñoz-Robredo et al (2013), confirmed that ethylene may have a role in some aspects of the grape ripening process. They also highlighted the potential use of VvACO1 , as a molecular marker for identifying grape veraison stages.…”
Section: Discussionmentioning
confidence: 56%
“…Likewise, their results of the evolution of both ACC (1-aminocyclopropane-1-carboxylic acid) content and ACO (ACC oxidase) activity strongly support the increase in ethylene production in grapevines during the early stage of cold stress. Results obtained by Muñoz-Robredo et al (2013), confirmed that ethylene may have a role in some aspects of the grape ripening process. They also highlighted the potential use of VvACO1 , as a molecular marker for identifying grape veraison stages.…”
Section: Discussionmentioning
confidence: 56%
“…Synthesis of ethylene biosynthesis begins with the conversion of methionine to S‐adenosylmethionine (SAM) by S‐adenosylmethionine synthase (SAMS) . SAM is then converted to 1‐amino syclopropane‐1‐carboxylic acid (ACC) by ACC synthase.…”
Section: List Of Proteins Identified To Be Associated With Flavor Vomentioning
confidence: 99%
“…SAM is then converted to 1‐amino syclopropane‐1‐carboxylic acid (ACC) by ACC synthase. Further, ACC is converted to ethylene in the presence of oxygen by ACC oxidase which is a rate limiting step . SAM can also be demethylated to form S ‐adenosyl‐ l ‐homocysteine and catabolized to homocysteine and adenosine by action of SAHH.…”
Section: List Of Proteins Identified To Be Associated With Flavor Vomentioning
confidence: 99%
“…For instance, EjACS1 and EjACO1 are specifically expressed in loquat fruit (Jiang et al, 2011), and LeACO1 is specifically expressed in tomato fruit (Barry et al, 1996). In grapes, there are at least 10 VvACS and 3 VvACO genes (Munoz-Robredo et al, 2013;Xu and Wang, 2012). The highest expression of VvACO1 gene was concomitant with an ethylene peak around veraison (Chervin et al, 2008;Munoz-Robredo et al, 2013;Pech et al, 2008).…”
mentioning
confidence: 99%
“…In grapes, there are at least 10 VvACS and 3 VvACO genes (Munoz-Robredo et al, 2013;Xu and Wang, 2012). The highest expression of VvACO1 gene was concomitant with an ethylene peak around veraison (Chervin et al, 2008;Munoz-Robredo et al, 2013;Pech et al, 2008). Moreover, there is little published data about the temporal and spatial expression of ACS and ACO genes in grapes.…”
mentioning
confidence: 99%